2018
DOI: 10.1080/0142159x.2018.1465533
|View full text |Cite
|
Sign up to set email alerts
|

Interest and perceived barriers toward careers in academic medicine among medical students at Alfaisal University – College of Medicine: A Saudi Arabian perspective

Abstract: AM careers were unpopular by students. Curricular, extracurricular and institutional measures should be implemented to rectify this dilemma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Past research in the area has often focused on a particular stage of career development,16 17 a particular population4 18 or a particular factor that affects equitable participation 19–21. Our aim is to examine this body of literature as a whole and to synthesise the full continuum of factors affecting equitable participation, retention and success in clinical academia at all stages of the pipeline.…”
Section: Review Objectivesmentioning
confidence: 99%
“…Past research in the area has often focused on a particular stage of career development,16 17 a particular population4 18 or a particular factor that affects equitable participation 19–21. Our aim is to examine this body of literature as a whole and to synthesise the full continuum of factors affecting equitable participation, retention and success in clinical academia at all stages of the pipeline.…”
Section: Review Objectivesmentioning
confidence: 99%
“…The interns' colleagues showed similar inclinations, with 46.6% indicating that having a pregnant colleague would increase their own workloads. The choices of medical students have also been shown to be affected by the lack of same-sex role models in certain medical fields (Abu-Zaid et al, 2018). The lack of same-sex role models in Arabic countries can be extreme, such as in Kuwait, where despite the fact that almost 62% of civil engineering undergraduates being female, 94 percent of the faculty members were male (Al-Fares and Al-Abdulmuhsen, 2008).…”
Section: The Environmentmentioning
confidence: 99%
“…Additionally, this study mentioned barriers perceived by female medical students in Saudi Arabia toward careers in academic medicine. These barriers included a lack of female role models in academic medicine and the presence of competing pressures to ful ll teaching/research, clinical duties, and family obligations [11]. On the other hand, one study from Abha, Saudi Arabia suggested that there was no relationship between gender and barriers toward conducting medical research in Saudi Arabia [12].…”
Section: Introductionmentioning
confidence: 99%